ANALISIS COMMOGNITIVE SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA BERBASIS KONTEKSTUAL PADA KONSEP BILANGAN BULAT - Halim, Abdul; Marsidi, Marsidi; Murtinasari, Frida (Universitas Insan Budi Utomo, 2025)
This study aims to explain students' cognitive abilities or we know it as the word commognitive which is a thinking process that is communicated both verbally and in writing. In solving contextual-based mathematical problems related to the concept of integers, of course it will be easy to solve the problem. This study is qualitative description. This study uses pretest, posttest, and interviews. The results obtained are that high-ability students fulfill the four stages of problem solving with commognitive components. At the stage of understanding the problem with the commognitive word use component, the subject is able to write down all the information that is known and the subject can determine what is asked in the question correctly. At the stage of making a plan with the commognitive word use component, visual mediator, narrative, the subject is able to mention the appropriate formula, the subject uses visual media according to the structure being asked, and students can describe the formula and use of visual media used correctly. While low-ability subjects fulfill three of the four stages of problem solving with the commognitive component. At the stage of understanding the problem, the subject is unable to write down all the information that is known correctly, but the subject can determine what is asked in the question correctly. at the stage of making a plan with the commognitive word use component, visual mediator, narrative the subject was unable to mention the formula that corresponds to the question, the subject did not use visual media and the student was unable to describe the formula correctly. At the stage of implementing the plan with commognitive the subject was unable to solve the question correctly and at the last stage of looking back with the commognitive component the subject was unable to determine the results of the question and the student was unable to explain again how to work on the question.